An Experimental Investigation of Sexual Scripts by Partner Gender: Anticipated Clitoral Stimulation and Partner Orgasm Pursuit Shape Women's Orgasm Expectations. - Wetzel, Grace M.; Wolfer, Carly; Carmichael, Cheryl L.; Sanchez, Diana T. (Archives of Sexual Behavior, 2025)
Research has found that bisexual women expect clitoral stimulation and orgasm more when hypothetically partnered with another woman versus a man, which is consistent with the widely documented heterosexual orgasm gap. The current research aims to (1) investigate "perceived partner orgasm pursuit" (i.e., the participant's perception that her partner is pursuing her orgasm) as a novel mechanism to explain this difference in orgasm expectations, and (2) demonstrate that manipulating the interpersonal sexual script with a male partner to include sufficient clitoral stimulation can increase orgasm expectations when women have sex with men. In Study 1, we found that bisexual or pansexual women (N = 457) partnered with a woman in a hypothetical scenario expected greater clitoral stimulation, partner pursuit of her orgasm, and likelihood of orgasm than those partnered with a man. In Study 2, bisexual or pansexual women (N = 362) who were partnered with a man in a hypothetical scenario that specified (1) clitoral stimulation or (2) opportunity to orgasm via her most reliable route expected her partner to pursue her orgasm and expected orgasm, at similar rates to women who were partnered with a woman whose sexual behavior was unspecified. On the contrary, women partnered with a man in a hypothetical scenario which specified vaginal intercourse only expected the lowest likelihood of orgasm. In both studies, condition predicted expected clitoral stimulation, which predicted perceived partner orgasm pursuit, which predicted orgasm expectations. This research suggests that sexual scripts explain differences in orgasm expectations by partner gender, and these expectations can be changed by shifting the sexual script at the interpersonal level to include sufficient opportunity for (and pursuit of) women's orgasm via clitoral stimulation. Findings are discussed in the context of contributors to and solutions for the orgasm gap.